PENDEKATAN TEORI POPULASI DALAM EKOSISTEM FINTECH - Champaca, Mychelia; Widodo, Deny Edy; Fitriasari, Rizka; Nurhidayat, Moch (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2023)
The development of fintech as a hybrid financial institution in the financial industry is growing rapidly, research on fintech studies mostly examines the role of fintech for the commercial financial institution market. Based on industry development statistics recorded by the OJK, this fintech development has proven to have a direct impact on the decline in banking performance as a whole, although the effect is not significant. Fintech directly encourages banking digitalization efforts that are already well established in the market, for example through the entry of fintech in the form of digital banks to compete in terms of ease of digital and collateral services. Meanwhile for microfinance institutions, competition from fintech entry is in the form of target markets that require easy access through smartphone applications or through access to collateral-free loans, as well as access to savings at almost no cost. The results of the bibliometric analysis from this research show that the stages of ecosystem development, that is, the assessment phase, the acceleration phase, and the augmentation phase, explain the ecological cycle of fintech organizations based on the Ecological Population Theory as the basis for fintech ecosystems.